1990
DOI: 10.1007/bf01664870
|View full text |Cite
|
Sign up to set email alerts
|

Fecal peritonitis: Microbial adherence to serosal mesothelium and resistance to peritoneal lavage

Abstract: Fecal contamination of the peritoneal cavity is a serious and potentially life-threatening event. While numerous models have been developed to study the pathogenesis of intraabdominal infection, to date, most investigations have failed to focus on the adherence of the contaminants to the serosal mesothelium. In the present investigation, the cecal ligation and puncture technique (CLP) was performed in Sprague-Dawley rats to study the following: (a) the kinetics of microbial adherence to the serosal mesothelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 25 publications
(23 reference statements)
2
40
0
3
Order By: Relevance
“…26,28 In our trial, the on-demand and planned relaparotomy strategies were equally apt to identify patients with remaining or new intra-abdominal infection after the index laparotomy. This also confirms that patients in the planned group were not more frequently determined to show positive findings due to differential verifica- (27) 27 (24) Cardiovascular disease 21 (18) 33 (29) Respiratory disease (chronic obstructive pulmonary disease) 14 (12) 17 (15) Renal disease 10 (9) 7 (6) Diabetes 9 (8) 11 ( …”
Section: Commentsupporting
confidence: 61%
See 1 more Smart Citation
“…26,28 In our trial, the on-demand and planned relaparotomy strategies were equally apt to identify patients with remaining or new intra-abdominal infection after the index laparotomy. This also confirms that patients in the planned group were not more frequently determined to show positive findings due to differential verifica- (27) 27 (24) Cardiovascular disease 21 (18) 33 (29) Respiratory disease (chronic obstructive pulmonary disease) 14 (12) 17 (15) Renal disease 10 (9) 7 (6) Diabetes 9 (8) 11 ( …”
Section: Commentsupporting
confidence: 61%
“…Other potential drawbacks of the planned relaparotomy strategy are the observed strong adherence of microbes residing in the peritoneum making them resistant to peritoneal lavage. 27 This reduces the effectiveness of the procedure and the damaging effects of lavage to the mesothelial layer may even reduce the innate resistance to infection. 26,28 In our trial, the on-demand and planned relaparotomy strategies were equally apt to identify patients with remaining or new intra-abdominal infection after the index laparotomy.…”
Section: Commentmentioning
confidence: 99%
“…Phagocytosis by PMNs results in ingestion and killing of a wide spectrum of microorganisms and is mediated by multiple cell surface receptors. The necessity for adequate ingestion and killing of microorganisms by phagocytes is demonstrated in a study carried out by Edmiston et al [5]: in a model based on cecal ligation and puncture technique in rats it was demonstrated that intraperitoneal/mesothelial microorganisms remained stable despite extended saline lavage. The study suggested that free particulates not firmly attached to the serosal mesothelium will be removed following lavage.…”
Section: Discussionmentioning
confidence: 99%
“…Lavage obviously decreases the microbial load of an infection, although bacteria sticking to the mesothelial cells are not removed [18]. The importance of removing debris and blood for the prevention of adhesion formation, although logic, has not been proven.…”
Section: Introductionmentioning
confidence: 99%